Recep Tayyip Erdogan and Donald Trump : Distinct Political Entities, Similar Leadership Styles? - Bieniek, Karol (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2017)
Since the center-periphery cleavage is widely used in the rhetoric of the two highly controversial political figures of R.T. Erdogan and D. Trump, it is interesting to examine their political careers. Both perform their political routes and construct their electoral appeal on the base of the center-periphery divide. The presented paper in general aims at qualifying the leadership style of both politicians. While the two leaders function in different political entities and traditions, their perception and understanding of politics seems to be quite similar